A pilot study to determine whether progestogen supplementation using dydrogesterone during the first trimester will reduce the incidence of gestational hypertension in primigravidae. (March 2014) - Zainul Rashid, M. R.; Lim, Jing Fen; Nawawi, Noorfaizahtul Hanim M.; Luqman, Melissha; Zolkeplai, Muhammad Faizuddin; Rangkuty, Harry Surya; Mohamad Nor, Natasha Ain; Tamil, Azmi; Shah, Shamsul Azhar; Tham, Seong Wai; Schindler, A. E.
Abstract Background: Gestational hypertension (GH) remains one of the main causes of high maternal and perinatal morbidity and mortality worldwide with the highest incidence among primigravidae of about 10%–15%. However, it was noted that the incidence of GH in primigravidae who conceived following assisted reproductive technique (ART) or intrauterine insemination (IUI) supplemented with dydrogesterone during the first trimester was low. Aim: To determine whether dydrogesterone supplementation during the first trimester can reduce the incidence of GH among primigravidae. Method: A prospective cross-sectional comparative study was undertaken in 2010 on 116 primigravidae (study group) who conceived following ART or IUI and supplemented with dydrogesterone up to 16 weeks gestation. They were matched for age and race at 16 weeks gestation with a control patient from the early pregnancy clinic who were primigravidae (n = 116) who conceived spontaneously without dydrogesterone supplementation. Findings: The incidence of GH in the study group was significantly lower than the control group (1.7% versus 12.9%, p = 0.001). The incidence of fetal distress was also significantly lower in the study group compared to the control group (4.3% versus 18.1%, p = 0.001). Interpretation: Dydrogesterone supplementation during the first trimester significantly reduced the incidence of GH and fetal distress in primigravidae.